2021
DOI: 10.1186/s13662-021-03265-4
|View full text |Cite
|
Sign up to set email alerts
|

A fractional order mathematical model for COVID-19 dynamics with quarantine, isolation, and environmental viral load

Abstract: COVID-19 or coronavirus is a newly emerged infectious disease that started in Wuhan, China, in December 2019 and spread worldwide very quickly. Although the recovery rate is greater than the death rate, the COVID-19 infection is becoming very harmful for the human community and causing financial loses to their economy. No proper vaccine for this infection has been introduced in the market in order to treat the infected people. Various approaches have been implemented recently to study the dynamics of this nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…COVID-19 infection in Nigeria has been studied by the authors in [ 19 ]. For more interesting work on COVID-19 using quarantine and isolation, robust analysis, etc, see [ 20 , 21 ]. Some recent literature on COVID-19 infection has been suggested in [ 22 26 ].…”
Section: Literaturementioning
confidence: 99%
“…COVID-19 infection in Nigeria has been studied by the authors in [ 19 ]. For more interesting work on COVID-19 using quarantine and isolation, robust analysis, etc, see [ 20 , 21 ]. Some recent literature on COVID-19 infection has been suggested in [ 22 26 ].…”
Section: Literaturementioning
confidence: 99%
“…Ali et al reported the optimal control of zika virus disease with the fractional derivatives ( Ali et al, 2022a , Ali et al, 2022b ). Similarly the utilization of the idea of optimal control for the control of COVID-19 can be seen in ( Aba Oud et al, 2021 ; S. W. Ahmad et al, 2021 ; Grigorieva et al, 2020 ; Zamir et al, 2020 ).…”
Section: Introductionmentioning
confidence: 95%
“…The novel Covid-19 is still a huge panic for people around the world. Various approaches are being considered to combat this deadly disease [1][2][3][4][5][6][7][8][9][10][11][12]. Noor et al examined a Stochastic Susceptible, Exposed, Infected and Recovered (SEIR) model of the novel coronavirus by applying various computational methods such as Euler Maruyama, Euler Stochastic and Runge Kutta Stochastic to study the dynamics of the mentioned model [13].…”
Section: Introductionmentioning
confidence: 99%